Minimizing problems and maximizing benefits from underground space use - Raymond L. Sterling (Underground Space, 2025)
For thousands of years, humans have used the underground for many purposes and we are now in an era when such uses are becoming more important to support our living patterns, our material needs and to improve the sustainability of our way of life. Many underground facilities serve their intended function well and have proven to have long lifetimes. Some have not been so successful for a variety of reasons or have been retired as no longer meeting the original purpose and not being suitable for conversion to another purpose. While the difference between success and failure is often tied to the specifics of a particular project, this paper seeks to extract some of the general principles that underlie the benefits or drawbacks of different types of underground space uses and how to maximize “success”. The paper is a mixture of the general and the specific because both play a role in success. The paper draws significantly from a recent study of the “lessons learned” from 42 worldwide underground facilities with an average of over 37 years of service mixed with other observations by the author from a career of studying underground space use and underground construction technologies.